Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume II - Planning Commission (Planning Commission, 1984)
Heads of Development-wise Outlays and Expenditure, Scheme-wise Outlays and Expenditure, Physical Targets and Achievements Minimum Needs Programme—Outlays and Expenditure, Minimum Needs Programme—Targets and Physical Achievements, Centrally Sponsored Schemes—Outlays, Special Component Plan for Scheduled Castes, State Plan Outlay under Tribal Sub-Plan, Tribal Sub-Plan—Physical Targets and Achievements, Twenty Point Programme—Outlays and Expenditure, Twenty Point Programme—Physical Targets and Achievements, Outlays and Expediture, Targets and Achievements, Sixth Plan Outlays and Expenditure, Distribution of District Sector Outlays
State Planning Board Trivandrum